Phenotype-based drug screening: An in vivo strategy to classify and identify the chemical compounds modulating zebrafish M-cell regeneration - Kumari, Ankita; Zeng, Xin-An; Rahaman, Abdul; Farooq, Muhammad Adil; Huang, Yanyan; Alee, Mahafooj; Yao, Runyu; Ali, Murtaza; Khalifa, Ibrahim; Badr, Omnia (Frontiers in Molecular Biosciences, 2022)
Recently, the phenotype-based drug screening (PDS) strategy has received good attention as an alternative approach for new drug discovery as well as for re-purposing of already developed drugs. Meanwhile, the zebrafish has emerged as a foremost vertebrate model for in vivo phenotypic screens and has contributed more widely to drug development and toxicity measurement even before. In this study, for the development of a modest and efficient in vivo assay to identify the M-cell modulating compounds, we incorporated the Tg(hsp: Gal4FF62A; UAS: nfsB-mCherry) transgenic zebrafish. Further, we performed the PDS strategy to screen US Drug Collection containing the 1260 compounds that were purchased from Micro-source Discovery System Inc. (USA). Consequently, we identified 14 compounds, including FDA-approved drugs, that were impairing the M-cell regeneration of zebrafish. Moreover, we also classified the whole drug library into 4 different groups based on the drug’s influences on the phenotype of M-cell regeneration. As well, we selected 4 FDA-approved drugs out of 14 compounds for computational analysis to elucidate their binding pattern with the signaling partner that may ultimately be responsible for regulating the axon regeneration process. Significantly, docking studies with PTEN, a widely known inhibitory signaling molecule of axon regeneration, revealed minor differences in binding affinity. This may predate PTEN as an interacting signaling molecule responsible for reducing axon regeneration. In conclusion, our screening strategy, together with re-purposing and computational analysis, will promote rapid translation of new therapeutics to improve knowledge of the toxicity profile of approved/non-approved drugs in an efficient manner.